Penerapan Algoritme Genetika untuk Optimasi Penjadwalan Jam Kerja Part-Time Studi Kasus Cafe Bingsoo Malang - Yogi Suwandy; Lailil Muflikhah; Tibyani Tibyani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Part-Time working hours or often called part-time working hours are a group of workers who alternately replace the other group after the work has ended. Part-time working hours are applied in an agency usually divide it in 3 shifts work, morning shift, day shift and night shift. Not a few students who choose Part-Time work for college while working to fill in the empty time in college because by working they can add pocket money and their experience. A manager or division chairman who plays a role in organizing work schedules should be meticulous in the distribution of employee shifts so that all employees get the same number of working hours. Scheduling is an activity to find the solution of a problem which will result in the optimal schedule of the schedule. Genetic algorithm is a method that has been applied by many researchers to get a solution of the problem scheduling. Genetic Algorithm used can provide accuracy value of 100% with a fitness value of 1 to 9 employees division waiters at Cafe Bingsoo Malang, the tests were performed using some of the best parameter values ​​such as population number 70, number of generation 70, crossover rate 0.6 and mutation rate 0.5 with fitness value obtained at 1.